Kekerasan Verbal dalam Dakwah (Studi Kasus Rekaman Ceramah Aman Abdurrahman) - Mustofa Hilmi; Zumrotul Choiriyah (LPPM Institut Pesantren KH. Abdul Chalim, 2022)
This research aims to determine the verbal abuses in speech. The main focus of this research is to know what are the forms of verbal abuse in Aman Abdurrahaman's